2000
DOI: 10.1116/1.1320809
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in field emission of silicon microtips by bias-assisted carburization

Abstract: Noise characteristics of emission current from conductive diamond-like carbon thin films coating on cone shaped silicon field emitters Ultrathin carbon layers with thicknesses below 50 Å have been deposited on silicon microtip arrays by bias-assisted carburization ͑BAC͒ using microwave plasma chemical vapor deposition. The tip radius of these silicon tips is reduced below 55 nm under low deposition temperature. The field emission characterization has been performed in a high-vacuum environment. An enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In particular, the conical Si nanostructures with their high aspect ratio and sharp tip radii are expected to be good candidates for field emitters [12] and electromagnetic sensors [13]. To date, the silicon cone structures have been formed using different methods such as patterned reactive ion etching (RIE) [14], laser beam irradiation [15], dry plasma etching [16] and hot plasma chemical vapor deposition (CVD) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the conical Si nanostructures with their high aspect ratio and sharp tip radii are expected to be good candidates for field emitters [12] and electromagnetic sensors [13]. To date, the silicon cone structures have been formed using different methods such as patterned reactive ion etching (RIE) [14], laser beam irradiation [15], dry plasma etching [16] and hot plasma chemical vapor deposition (CVD) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The "top-down" technique is straightforward and much easier for the fabrication of vertical well-aligned nanocolumns. For example, one can use optical lithography to prepare nanocolumns with 100 nm in diameter [31][32][33] or use nanolithography to prepare nanocolumns with 30 nm in diameter [34]. Very recently, Yoshida et al reported the fabrication of GaN nanocolumns by simple reactive ion etching (RIE) [35] without the lithography process.…”
mentioning
confidence: 99%
“…The microgeometry of these nanostructures demonstrated how some of the parameters of the Fowler-Nordheim equation, 2 especially the field enhancement factor, used to describe field emission in metals, could be tailored to achieve lower threshold voltages for electron emission. The material, 3 its microstructure, 4 the microgeometry ͑that is, whether the emitter is a tip, tube or rod͒, 5,6 any adsorbed species and surface modifications, 7,8 and electrical and other physical properties of the emitting material were thoroughly studied to give us an insight into this phenomenon of field emission. However, these nanostructures are often supported on attractive substrates such as silicon, for future integration to the device technology, whose role in determining the emission efficiency has been unclear.…”
mentioning
confidence: 99%
“…SiNW, multiwall CNTs ͑MWCNT͒, and SiCN nanocrystalline thin films and nanorods were deposited on doped Si substrates namely, n ϩ (resistivityϳ2 -5 m⍀ cm), n (resistivityϳ1 -10 ⍀ cm), and p type (resistivityϳ1 -10 ⍀ cm). The field emission properties were measured on a parallel-plate diode type device structure, 8 where the nanostructures grown on silicon served as the cathode and an indium tin oxide coated glass plate served as the anode. The distance between these two electrodes could be controlled, and was kept at ϳ50 m. This distance was used to calculate the apparent field at the tip.…”
mentioning
confidence: 99%